Analisis Pola Pembelian Konsumen dengan Menggunakan Market Basket Analysis ( Studi Kasus Indomaret Tentara Pelajar, Sleman, Yogyakarta) - Harlinda Rasvi Nabela (Fakultas Teknik dan Rekayasa, 2025)
Every customer or consumer has different wants and needs, but the way they behave to fulfill these needs remains the same, namely they want to maximize their satisfaction by purchasing the goods or services they need. By looking at consumer purchasing patterns, sellers can find out customer purchasing behavior patterns. This pattern can help sellers in developing sales strategies. The aim of this research is to analyze the purchasing patterns of Indomaret Student Army consumers by applying the Association Rule - Market Basket Analysis (AR-MBA) method. This shopping cart analysis helps find out how the goods or services purchased by customers relate to each other. The results obtained from the Rapidminer software show that there are 6 combinations of purchasing patterns from department 1 mineral water, department 4 snacks, department 11 bread, and department 23 biscuits. Keywords: Association rules, Market Basket Analysis, Purchase Patterns, Rapidminer